Nonaqueous electrolyte power storage element

JP2025016289APending Publication Date: 2025-01-31GS YUASA CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023119471
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-21
Publication Date
2025-01-31

AI Technical Summary

Benefits of technology

【0009】 本発明の一側面に係る非水電解質蓄電素子は、ポリアニオン構造を有するリチウム遷移金属化合物を含む正極活物質、及び不飽和環状カーボネートを含有する非水電解質を用い、且つ負極活物質層の表面積に対する不飽和環状カーボネートの非水電解質中における量が小さく構成された非水電解質蓄電素子であって、長期保存後の容量維持率が大きい。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025016289000001_ABST
    Figure 2025016289000001_ABST
Patent Text Reader

Abstract

To provide a nonaqueous electrolyte power storage element of which the capacity maintenance rate after long-term storage is improved.SOLUTION: A nonaqueous electrolyte power storage element comprises: a positive electrode containing a lithium transition metal compound having a polyanion structure; a negative electrode including a negative electrode active material layer containing a negative electrode active material; and a nonaqueous electrolyte. The nonaqueous electrolyte contains an unsaturated cyclic carbonate and a dinitrile compound. A ratio AC / S of an amount AC [mmol] of the unsaturated cyclic carbonate in the nonaqueous electrolyte with respect to a surface area S [m2] of the negative electrode active material layer is less than 0.164 mmol / m2, and a ratio AN / AL of an amount AN [mmol] of the dinitrile compound in the nonaqueous electrolyte with respect to an amount AL [mmol] of the lithium transition metal compound in the positive electrode is equal to or more than 0.010.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a non-aqueous electrolyte electricity storage element. [Background technology]

[0002] Non-aqueous electrolyte secondary batteries, such as lithium ion non-aqueous electrolyte secondary batteries, are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc., due to their high energy density. Non-aqueous electrolyte secondary batteries generally include an electrode assembly having a pair of electrodes electrically isolated by a separator, and a non-aqueous electrolyte interposed between the electrodes, and are configured to charge and discharge by transferring charge-transporting ions between the electrodes. In addition, capacitors such as lithium ion capacitors and electric double layer capacitors are also widely used as storage elements other than non-aqueous electrolyte secondary batteries.

[0003] Lithium transition metal compounds having a polyanion structure, such as lithium iron phosphate, are known as positive electrode active materials used in nonaqueous electrolyte storage elements. In addition, in order to improve the various properties of nonaqueous electrolyte storage elements, nonaqueous electrolytes containing vinylene carbonate are sometimes used (Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2017-097995 A Summary of the Invention [Problem to be solved by the invention]

[0005] It is known that an unsaturated cyclic carbonate such as vinylene carbonate, when contained in a non-aqueous electrolyte, forms a coating film capable of protecting the negative electrode surface, thereby contributing to improving the durability of a non-aqueous electrolyte storage element. On the other hand, if the coating film derived from the unsaturated cyclic carbonate on the negative electrode surface becomes too thick, the resistance of the non-aqueous electrolyte storage element may increase.

[0006] In this regard, the present inventors have been studying how to reduce the amount of unsaturated cyclic carbonate in the nonaqueous electrolyte relative to the surface area of ​​the negative electrode active material layer in order to reduce the resistance of the nonaqueous electrolyte storage element. However, when the amount of unsaturated cyclic carbonate in the nonaqueous electrolyte relative to the surface area of ​​the negative electrode active material layer is reduced, and a positive electrode active material containing a lithium transition metal compound having the above-mentioned polyanion structure is used, there have been occasional instances where the capacity of the nonaqueous electrolyte storage element is significantly reduced after being stored for a relatively long period of time.

[0007] The present invention has been made in light of the above circumstances, and has an object to provide a nonaqueous electrolyte storage element that uses a positive electrode active material containing a lithium transition metal compound having a polyanion structure, and a nonaqueous electrolyte containing an unsaturated cyclic carbonate, and is configured such that the amount of unsaturated cyclic carbonate in the nonaqueous electrolyte relative to the surface area of ​​a negative electrode active material layer is small, and that has a high capacity retention rate after long-term storage. [Means for solving the problem]

[0008] A non-aqueous electrolyte storage element according to one aspect of the present invention comprises a positive electrode containing a lithium transition metal compound having a polyanion structure, a negative electrode having a negative electrode active material layer containing a negative electrode active material, and a non-aqueous electrolyte, the non-aqueous electrolyte containing an unsaturated cyclic carbonate and a dinitrile compound, and the surface area S [m 2 Amount A of the unsaturated cyclic carbonate in the nonaqueous electrolyte C [mmol] Ratio A C / S is 0.164mmol / m 2 and the amount A of the lithium transition metal compound in the positive electrode is less than L [mmol], the amount A of the dinitrile compound in the nonaqueous electrolyte N [mmol] Ratio A N / A L is greater than or equal to 0.010. Effect of the Invention

[0009] A nonaqueous electrolyte storage element according to one aspect of the present invention is a nonaqueous electrolyte storage element that uses a positive electrode active material including a lithium transition metal compound having a polyanion structure, and a nonaqueous electrolyte containing an unsaturated cyclic carbonate, and is configured such that the amount of unsaturated cyclic carbonate in the nonaqueous electrolyte relative to the surface area of ​​a negative electrode active material layer is small, and that has a high capacity retention rate after long-term storage. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a perspective view showing one embodiment of a nonaqueous electrolyte electricity storage element according to the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing one embodiment of an electricity storage device formed by assembling a plurality of nonaqueous electrolyte electricity storage elements according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] First, an overview of the nonaqueous electrolyte electricity storage element disclosed in this specification will be described.

[0012] [1] A non-aqueous electrolyte storage element according to one aspect of the present invention comprises a positive electrode containing a lithium transition metal compound having a polyanion structure, a negative electrode having a negative electrode active material layer containing a negative electrode active material, and a non-aqueous electrolyte, the non-aqueous electrolyte containing an unsaturated cyclic carbonate and a dinitrile compound, and the surface area S [m 2 Amount A of the unsaturated cyclic carbonate in the nonaqueous electrolyte C [mmol] Ratio A C / S is 0.164mmol / m 2 and the amount A of the lithium transition metal compound in the positive electrode is less than L [mmol], the amount A of the dinitrile compound in the nonaqueous electrolyte N [mmol] Ratio A N / A L is greater than or equal to 0.010.

[0013] The nonaqueous electrolyte storage element described in [1] above has a high capacity retention rate after long-term storage. Although the reason for this is not clear, the following reasons are presumed. In a non-aqueous electrolyte storage element using a positive electrode active material containing a lithium transition metal compound having a polyanion structure, the transition metal element cation contained in the lithium transition metal compound may dissolve in the non-aqueous electrolyte and precipitate on the negative electrode surface. This may cause cracks in the coating on the negative electrode surface derived from the unsaturated cyclic carbonate. In particular, in a non-aqueous electrolyte storage element in which the amount of unsaturated cyclic carbonate in the non-aqueous electrolyte relative to the surface area of ​​the negative electrode active material layer is set small, the coating on the negative electrode surface derived from the unsaturated cyclic carbonate is likely to become thin, and there are many places (coating defects) in the coating through which the non-aqueous electrolyte can easily pass, so that the coating is likely to crack. When cracks occur in the coating, the coating is reformed in the cracked portion, and the charge transport ions in the non-aqueous electrolyte are consumed, so that the capacity of the non-aqueous electrolyte storage element may gradually decrease with long-term storage.

[0014] In contrast, the nonaqueous electrolyte storage element described in [1] has a surface area S [m 2 Amount A of the unsaturated cyclic carbonate in the nonaqueous electrolyte C [mmol] Ratio A C When the ratio A / S is less than the upper limit, the coating film derived from the unsaturated cyclic carbonate tends to become thin on the negative electrode surface, but since the non-aqueous electrolyte contains a dinitrile compound, it is possible to suppress a decrease in capacity retention rate due to the precipitation of the transition metal element cation contained in the lithium transition metal compound on the negative electrode surface. More specifically, the transition metal element cation is coordinated between two cyano groups of the dinitrile compound in the non-aqueous electrolyte and chelated, thereby suppressing the precipitation of the transition metal element cation on the negative electrode surface. In addition, the amount A of the lithium transition metal compound in the positive electrode L [mmol], the amount A of the dinitrile compound in the nonaqueous electrolyte N [mmol] Ratio A N / A Lis equal to or greater than the lower limit, the transition metal element cation derived from the lithium transition metal compound can be sufficiently chelated. Therefore, the nonaqueous electrolyte storage element described in [1] above has a high capacity retention rate after long-term storage.

[0015] According to the study by the present inventors, the surface area S [m 2 Amount A of the unsaturated cyclic carbonate in the nonaqueous electrolyte C [mmol] Ratio A C When / S is increased to a certain level or more, the amount A of the dinitrile compound in the nonaqueous electrolyte N [mmol] Ratio A N / A L It was confirmed by the test examples (reference examples, etc.) described later that the effect of increasing the capacity retention rate after long-term storage cannot be obtained by adjusting the ratio A to the above lower limit or more. N / A L The provision of the above ratio A C By applying this in combination with the provision of / S, a nonaqueous electrolyte storage element can be provided in which the capacity retention rate after long-term storage is significantly improved, as a specific effect of such a combination.

[0016] The term "dinitrile compound" refers to a compound having two cyano groups in the molecule. N The amount of the dinitrile compound A is the amount in the nonaqueous electrolyte taken out from the nonaqueous electrolyte storage element. N [mmol] is the amount of substance determined by subjecting the non-aqueous electrolyte to gas chromatography mass spectrometry (GC-MS analysis) in accordance with JIS-K-0123 (2018). Specifically, the mass of the non-aqueous electrolyte and the amount of substance of the dinitrile compound are measured by the following method. The mass A of the nonaqueous electrolyte storage element is measured. Then, the nonaqueous electrolyte storage element is disassembled, and the nonaqueous electrolyte is collected. All parts of the nonaqueous electrolyte storage element other than the nonaqueous electrolyte are washed with dimethyl carbonate and thoroughly dried under reduced pressure at room temperature. The mass B of all parts of the nonaqueous electrolyte storage element other than the nonaqueous electrolyte after vacuum drying is measured. The difference between mass A and mass B is the mass C of the nonaqueous electrolyte contained in the nonaqueous electrolyte storage element. Meanwhile, the concentration (mass%) of the dinitrile compound in the nonaqueous electrolyte is obtained by GC-MS analysis using the nonaqueous electrolyte collected during disassembly. The mass D of the dinitrile compound in the nonaqueous electrolyte is calculated from the concentration of the dinitrile compound and the mass C of the nonaqueous electrolyte. The mass D of the dinitrile compound in the nonaqueous electrolyte is divided by the molecular weight of the dinitrile compound to obtain the amount of substance of the dinitrile compound in the nonaqueous electrolyte.

[0017] Surface area of ​​the negative electrode active material layer S [m 2 ] is the BET specific surface area of ​​the negative electrode active material layer, B [m 2 / g] and the mass of the negative electrode active material layer is E [g], the "BET specific surface area" of the negative electrode active material layer is a value obtained from an adsorption isotherm using a nitrogen gas adsorption method. Specifically, the BET specific surface area B and the mass E of the negative electrode active material layer are measured by the following method. First, the nonaqueous electrolyte storage element is discharged at a constant current of 0.05 C to the lower limit voltage for normal use. Here, "normal use" refers to the case where the nonaqueous electrolyte storage element is used under the charge / discharge conditions recommended or specified for the nonaqueous electrolyte storage element. The nonaqueous electrolyte storage element is disassembled, the negative electrode is removed and used as the working electrode, and a test battery is assembled with metallic Li as the counter electrode. The negative electrode potential is measured at a current of 10 mA per 1 g of negative electrode active material until the negative electrode potential reaches 2.0 V vs. Li / Li. +The battery is discharged at a constant current until the negative electrode reaches a constant current of 1000 V. Here, "discharge" in the test battery refers to an oxidation reaction in which charge transport ions such as lithium ions are released from the negative electrode, which is the working electrode. The test battery is disassembled again, and the negative electrode is taken out. The non-aqueous electrolyte attached to the taken-out negative electrode is thoroughly washed using dimethyl carbonate, and the negative electrode is dried under reduced pressure at room temperature for 24 hours, and then a predetermined area of ​​the negative electrode active material layer is taken out. The mass of the taken negative electrode active material layer and the area of ​​the negative electrode active material layer in the above-mentioned predetermined area are measured to determine the mass of the negative electrode active material layer per unit area. The mass E of the negative electrode active material layer is determined from the mass of the negative electrode active material layer per unit area and the area of ​​the negative electrode active material layer provided on the negative electrode. Here, the "area of ​​the negative electrode active material layer provided on the negative electrode" is defined as the area of ​​the part facing the positive electrode active material layer via the separator. On the other hand, the negative electrode active material layer of the portion not used to calculate the mass E of the negative electrode active material layer is used to measure the adsorption isotherm by nitrogen gas adsorption method within the range of relative pressure P / P0 (P0 = approximately 770 mmHg) from 0 to 1. This measurement is performed using Quantachrome's "autosorb iQ". Five points are extracted from the region of P / P0 = 0.06 to 0.3 of the obtained adsorption isotherm, and a BET plot is performed, and the BET specific surface area B is calculated from the y-intercept and slope of the straight line.

[0018] "Amount of lithium transition metal compound A L " is a value obtained by dismantling the nonaqueous electrolyte storage element, extracting the lithium transition metal compound, and converting the amount of substance of the transition metal element contained in the lithium transition metal compound into the amount of substance of the lithium transition metal compound. Specifically, the amount of substance of the transition metal element contained in the lithium transition metal compound is measured by the following method. First, the nonaqueous electrolyte storage element is discharged at a constant current of 0.05C to the lower limit voltage during normal use. Here, "normal use" refers to the case where the nonaqueous electrolyte storage element is used by adopting the charge / discharge conditions recommended or specified for the nonaqueous electrolyte storage element. The nonaqueous electrolyte storage element is disassembled, and the positive electrode is taken out. The nonaqueous electrolyte attached to the taken positive electrode is thoroughly washed using dimethyl carbonate, and the positive electrode active material layer is dried under reduced pressure at room temperature for 24 hours, and then a predetermined range of the positive electrode active material layer is collected. The mass of the collected positive electrode active material layer and the area of ​​the positive electrode active material layer in the above-mentioned predetermined range are measured to determine the mass of the positive electrode active material layer per unit area. The mass of the positive electrode active material layer is determined from the mass of the positive electrode active material layer per unit area and the area of ​​the positive electrode active material layer provided on the positive electrode. On the other hand, the positive electrode active material layer taken from the part not used to determine the mass of the positive electrode active material layer is used to perform thermogravimetry (TG measurement) under an air atmosphere to determine the content (mass%) of the lithium transition metal compound contained in the positive electrode active material layer. The mass of the lithium transition metal compound contained in the positive electrode active material layer is determined from the mass of the positive electrode active material layer and the content (mass%) of the lithium transition metal compound contained in the positive electrode active material layer. Next, the positive electrode active material layer taken from the part not used to determine the mass of the positive electrode active material layer and for the TG measurement is used to perform X-ray diffraction measurement to identify the crystal structure of the lithium transition metal compound. On the other hand, in order to determine the mass of the positive electrode active material layer, the lithium transition metal compound contained in the positive electrode active material layer taken from the part not used for the TG measurement and the X-ray diffraction measurement is completely dissolved in an acid capable of dissolving the lithium transition metal compound by a microwave decomposition method. Next, this solution is diluted to a certain amount with pure water to obtain a measurement solution. Then, the concentrations of all the transition metal elements contained in the measurement solution are measured by inductively coupled plasma atomic emission spectrometry (ICP), the transition metal elements contained in the lithium transition metal compound are identified, and their molar masses are calculated. The mass of the lithium transition metal compound is divided by the molar mass to calculate the amount of substance of the transition metal element contained in the lithium transition metal compound.The composition formula of the lithium transition metal compound is determined from the calculated amount of substance of the transition metal element contained in the lithium transition metal compound and the identified crystal structure, and the amount of substance of the transition metal element contained in the lithium transition metal compound is converted into the amount of substance of the lithium transition metal compound.

[0019] "Amount of unsaturated cyclic carbonate in non-aqueous electrolyte A C " is obtained by dismantling the nonaqueous electrolyte storage element and converting the mass of the unsaturated cyclic carbonate contained in the extracted nonaqueous electrolyte into the amount of substance of the unsaturated cyclic carbonate. The mass of the unsaturated cyclic carbonate is determined by subjecting the nonaqueous electrolyte to gas chromatography mass spectrometry (GC-MS analysis) in accordance with JIS-K-0123 (2018). Specifically, the mass of the nonaqueous electrolyte and the amount of substance of the unsaturated cyclic carbonate are measured by the following method. The mass A of the nonaqueous electrolyte storage element is measured. Then, the nonaqueous electrolyte storage element is disassembled, and the nonaqueous electrolyte is collected. All parts of the nonaqueous electrolyte storage element other than the nonaqueous electrolyte are washed with dimethyl carbonate and thoroughly dried under reduced pressure at room temperature. The mass B of all parts of the nonaqueous electrolyte storage element other than the nonaqueous electrolyte after vacuum drying is measured. The difference between mass A and mass B is the mass C of the nonaqueous electrolyte contained in the nonaqueous electrolyte storage element. Meanwhile, the concentration (mass%) of the unsaturated cyclic carbonate in the nonaqueous electrolyte is obtained by GC-MS analysis using the nonaqueous electrolyte collected during disassembly. The mass E of the unsaturated cyclic carbonate in the nonaqueous electrolyte is calculated from the concentration of the unsaturated cyclic carbonate and the mass C of the nonaqueous electrolyte. The mass E of the unsaturated cyclic carbonate in the nonaqueous electrolyte is divided by the molecular weight of the unsaturated cyclic carbonate to obtain the amount of substance of the unsaturated cyclic carbonate in the nonaqueous electrolyte.

[0020] [2] In the nonaqueous electrolyte storage element according to [1], C / S is 0.055mmol / m 2 It may be super.

[0021] In the nonaqueous electrolyte storage element described in [2] above, a coating film derived from the unsaturated cyclic carbonate is appropriately formed on the negative electrode surface, and therefore the capacity retention rate after long-term storage is higher.

[0022] [3] In the nonaqueous electrolyte storage element according to the above [1] or [2], the dinitrile compound may be succinonitrile or adiponitrile.

[0023] In the nonaqueous electrolyte storage element described in [3] above, the dinitrile compound is succinonitrile or adiponitrile, which easily chelates the transition metal element cation derived from the lithium transition metal compound, and therefore the capacity retention rate after long-term storage is greater.

[0024] Hereinafter, a nonaqueous electrolyte electricity storage element, an electricity storage device, a method for manufacturing a nonaqueous electrolyte electricity storage element according to one embodiment of the present invention, and other embodiments will be described in detail. Note that the names of the components (components) used in each embodiment may differ from the names of the components (components) used in the background art.

[0025] [Non-aqueous electrolyte energy storage element] A nonaqueous electrolyte storage element according to one embodiment of the present invention includes an electrode assembly in which a positive electrode and a negative electrode are stacked with a separator interposed therebetween, a nonaqueous electrolyte, and a container for accommodating the electrode assembly and the nonaqueous electrolyte. The electrode assembly is usually a laminated type in which a plurality of positive electrodes and a plurality of negative electrodes are stacked with a separator interposed therebetween, or a wound type in which a positive electrode and a negative electrode are stacked with a separator interposed therebetween and wound. The nonaqueous electrolyte exists in a state in which it is contained in the positive electrode, the negative electrode, and the separator. As an example of a storage element, a nonaqueous electrolyte secondary battery (hereinafter, also simply referred to as a "secondary battery") will be described.

[0026] [Positive electrode] The positive electrode has a positive electrode substrate and a positive electrode active material layer laminated on the positive electrode substrate directly or via an intermediate layer.

[0027] The positive electrode substrate is conductive. Whether or not it has "conductivity" is determined by whether the volume resistivity measured in accordance with JIS-H-0505 (1975) is 10 -2 The threshold value is Ω·cm. The material of the positive electrode substrate is a metal such as aluminum, titanium, tantalum, stainless steel, or an alloy thereof. Among these, aluminum or an aluminum alloy is preferred from the viewpoints of potential resistance, high conductivity, and cost. The positive electrode substrate may be a foil, a vapor deposition film, a mesh, a porous material, etc., and a foil is preferred from the viewpoint of cost. Therefore, aluminum foil or an aluminum alloy foil is preferred as the positive electrode substrate. Examples of aluminum or an aluminum alloy include A1085, A3003, A1N30, etc., as specified in JIS-H-4000 (2014) or JIS-H-4160 (2006).

[0028] The average thickness of the positive electrode substrate is preferably 3 μm to 50 μm, more preferably 5 μm to 40 μm, further preferably 8 μm to 30 μm, and particularly preferably 10 μm to 25 μm. By setting the average thickness of the positive electrode substrate within the above range, it is possible to increase the strength of the positive electrode substrate and to increase the energy density per volume of the nonaqueous electrolyte storage element.

[0029] The intermediate layer is a layer disposed between the positive electrode substrate and the positive electrode active material layer. The intermediate layer contains a conductive agent such as carbon particles to reduce the contact resistance between the positive electrode substrate and the positive electrode active material layer. The configuration of the intermediate layer is not particularly limited, and may contain, for example, a binder and a conductive agent.

[0030] <Cathode active material layer> In one embodiment of the present invention, the positive electrode active material layer contains a positive electrode active material. The positive electrode active material layer may further contain optional components such as a conductive agent, a binder, a thickener, and a filler, as necessary.

[0031] (Composition of Positive Electrode Active Material) In one embodiment of the present invention, the positive electrode active material is a compound capable of absorbing and releasing charge transport ions such as lithium ions, and includes a lithium transition metal compound having a polyanion structure (hereinafter also referred to as a polyanion-based compound).

[0032] Polyanion compounds include oxoacid anions (PO4 3- , SO4 2- , SiO4 4- , BO3 3- , VO4 3- The oxo acid anion is a condensed anion (P2O7 4- , P3O 10 5- The polyanionic compound may have an olivine-type crystal structure. The polyanionic compound preferably contains an alkali metal element ion or an alkaline earth metal element ion and a transition metal element cation, and may further contain other elements (e.g., halogen elements, etc.). The alkali metal ion or alkaline earth metal ion contained in the polyanionic compound is preferably a lithium ion, a sodium ion, or a potassium ion, and more preferably a lithium ion. The transition metal element cation contained in the polyanionic compound is preferably an iron cation, a manganese cation, a nickel cation, or a cobalt cation, and more preferably an iron cation or a manganese cation. The oxo acid anion contained in the polyanionic compound is preferably a phosphate anion (PO4 3- ) or silicate anion (SiO4 4- ) is preferred, and phosphate anion (PO4 3- ) is more preferred.

[0033] The polyanionic compound is preferably a compound represented by the following formula (1). Li a M b (A.O. c ) d X e (1) In formula (1), M is at least one transition metal element. A is at least one selected from B, Al, Si, P, S, Cl, Ti, V, Cr, Mo, and W. X is at least one halogen element. a, b, c, d, and e are numbers satisfying 0 < a ≤ 3, 0 < b ≤ 2, 2 ≤ c ≤ 4, 1 ≤ d ≤ 3, and 0 ≤ e ≤ 1. a, b, c, d, and e may all be integers or decimals.

[0034] As M in formula (1), any one of Fe, Mn, Ni, and Co, or a combination of two or more of these is preferable. As M, Fe, Mn, or a combination thereof is more preferable, and Fe is even more preferable. Further, the content of Fe in M is preferably 50 mol% or more, more preferably 70 mol% or more, 90 mol% or more, or 99 mol% or more. As A, P is preferable. As X, F is preferable. In one embodiment, a = 1, b = 1, c = 4, d = 1, and e = 0 may be preferable in some cases.

[0035] Specific examples of the polyanion-based compound include, for example, LiFePO4, LiCoPO4, LiFe 0.5 Co 0.5 PO4, LiMnPO4, LiNiPO4, LiMn 0.5 Fe 0.5 PO4, LiCrPO4, LiFeVO4, Li2FeSiO4, Li2Fe2(SO4)3, LiFeBO3, LiFePO 3.9 F 0.2 , Li3V2(PO4)3, Li2MnSiO4, Li2CoPO4F, etc. Atoms or polyanions in these polyanion-based compounds may be partially substituted with other atoms or anion species. The polyanion-based compound may be used alone or in combination of two or more.

[0036] The polyanionic compound is usually a particle (powder). The polyanionic compound may be a single particle (single particle) in which a plurality of primary particles are not aggregated, but is preferably a secondary particle formed by aggregation of a plurality of primary particles. The average particle size (average secondary particle size) of the polyanionic compound is not particularly limited, but for example, the lower limit is preferably 0.1 μm, more preferably 1 μm, and even more preferably 3 μm. On the other hand, the upper limit of the average particle size of the polyanionic compound is preferably 20 μm, more preferably 16 μm, and even more preferably 12 μm. By setting the average particle size of the polyanionic compound to be equal to or greater than the lower limit, the production or handling of the polyanionic compound becomes easy. By setting the average particle size of the polyanionic compound to be equal to or less than the upper limit, the electronic conductivity of the positive electrode active material layer is improved. In addition, the average particle size of the polyanionic compound may be equal to or greater than any of the lower limits and equal to or less than any of the upper limits. The "average particle size" of the polyanionic compound and the negative electrode active material described later means a value at which the volume-based cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) is 50%, based on the particle size distribution measured by a laser diffraction / scattering method for a solution obtained by diluting particles with a solvent in accordance with JIS-Z-8825 (2013).

[0037] In order to obtain the polyanion compound with a predetermined particle size, a pulverizer, a classifier, etc. are used. Examples of the pulverization method include a method using a mortar, a ball mill, a sand mill, a vibration ball mill, a planetary ball mill, a jet mill, a counter jet mill, a swirling airflow type jet mill, or a sieve. When pulverizing, wet pulverization in the presence of water or an organic solvent such as hexane can also be used. As a classification method, a sieve, an air classifier, etc. are used as necessary for both dry and wet methods.

[0038] The polyanion-based compound may be used in the form of a granule coated with a carbon material (hereinafter, also referred to as "carbon-coated positive electrode active material particles") from the viewpoint of electronic conductivity, etc. That is, in one embodiment of the present invention, the positive electrode active material may include carbon-coated positive electrode active material particles having a polyanion-based compound as a core.

[0039] In the carbon-coated positive electrode active material particles, a part of the carbon material may be present inside the particles containing the polyanion-based compound. In the carbon-coated positive electrode active material particles, there may be a part that is not coated with the carbon material (for example, a part where the polyanion-based compound is exposed).

[0040] The carbon-coated positive electrode active material particles can exhibit sufficient electron conductivity between particles because the carbon material coats the polyanion compound. The carbon material is, for example, an inorganic material with a carbon element content of 80% by mass or more and 100% by mass or less. The carbon element content in the carbon material may be 90% by mass or more, or may be 95% by mass or more. Examples of elements other than the carbon element that may be contained in the carbon material include oxygen element, hydrogen element, and nitrogen element. Examples of the carbon material include graphite and non-graphitic carbon.

[0041] The carbon material content in the carbon-coated positive electrode active material particles is preferably 0.1% by mass or more and 20% by mass or less, more preferably 0.2% by mass or more and 10% by mass or less, even more preferably 0.3% by mass or more and 5% by mass or less, and even more preferably 0.5% by mass or more and 2% by mass or less. By setting the carbon material content in the carbon-coated positive electrode active material particles to the lower limit or more, it is possible to increase the electronic conductivity, etc. By setting the carbon material content in the carbon-coated positive electrode active material particles to the upper limit or less, it is possible to increase the polyanion compound content, and to increase the discharge capacity per volume of the nonaqueous electrolyte storage element, etc.

[0042] The positive electrode active material layer may further contain other positive electrode active materials other than the polyanion-based compound. As the other positive electrode active materials, various conventionally known positive electrode active materials can be used. However, the content of the polyanion-based compound with respect to all the positive electrode active materials (the total of the polyanion-based compound and other positive electrode active materials) contained in the positive electrode active material layer is preferably 90% by mass or more, more preferably 99% by mass or more, and even more preferably 100% by mass. In this way, by substantially forming the positive electrode active material only from the polyanion-based compound, the effect of this configuration of increasing the capacity retention rate after long-term storage is significantly exhibited.

[0043] The content of the positive electrode active material in the positive electrode active material layer is preferably 50% by mass to 99% by mass, more preferably 70% by mass to 98% by mass, and even more preferably 80% by mass to 95% by mass. By setting the content of the positive electrode active material within the above range, it is possible to increase the discharge capacity of the nonaqueous electrolyte storage element.

[0044] (Other configurations) The conductive agent is not particularly limited as long as it is a material having electrical conductivity. Examples of such conductive agents include carbon materials, metals, conductive ceramics, and the like. Examples of carbon materials include graphite, non-graphitic carbon, graphene-based carbon, and the like. Examples of non-graphitic carbon include carbon nanofibers, pitch-based carbon fibers, carbon black, and the like. Examples of carbon black include furnace black, acetylene black, ketjen black, and the like. Examples of graphene-based carbon include graphene, carbon nanotubes (CNT), fullerene, and the like. Examples of the shape of the conductive agent include powder and fiber. As the conductive agent, one of these materials may be used alone, or two or more of them may be mixed and used. In addition, these materials may be used in a composite form. For example, a material in which carbon black and CNT are composited may be used. Among these, carbon black is preferable from the viewpoint of electronic conductivity and coatability, and acetylene black is preferable among them.

[0045] The content of the conductive agent in the positive electrode active material layer is preferably 1% by mass or more and 10% by mass or less, and more preferably 3% by mass or more and 9% by mass or less. By setting the content of the conductive agent in the above range, the energy density of the energy storage element can be increased. Note that the content of the conductive agent does not include the carbon material (carbon material coating the polyanion compound) contained in the carbon-coated positive electrode active material particles.

[0046] Examples of binders include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc.

[0047] The content of the binder in the positive electrode active material layer is preferably from 1% by mass to 10% by mass, and more preferably from 3% by mass to 9% by mass. By setting the content of the binder in the above range, the positive electrode active material can be stably maintained.

[0048] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC) and methyl cellulose. When the thickener has a functional group that reacts with lithium or the like, the functional group may be deactivated in advance by methylation or the like. When a thickener is used, the content of the thickener in the positive electrode active material layer may be, for example, 0.1% by mass or more and 8% by mass or less, and may be 5% by mass or less, or 1% by mass or less. The positive electrode active material layer may not contain a thickener.

[0049] The filler is not particularly limited. Examples of the filler include polyolefins such as polypropylene and polyethylene, inorganic oxides such as silicon dioxide, alumina, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, poorly soluble ion crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, and artificial products thereof. When a filler is used, the content of the filler in the positive electrode active material layer can be, for example, 0.1% by mass or more and 8% by mass or less, and can also be 5% by mass or less or 1% by mass or less. The positive electrode active material layer does not need to contain a filler.

[0050] The positive electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W, as components other than the positive electrode active material particles, other positive electrode active materials, conductive agents, binders, thickeners, and fillers.

[0051] [Negative electrode] The negative electrode has a negative electrode substrate and a negative electrode active material layer disposed on the negative electrode substrate directly or via an intermediate layer. The configuration of the intermediate layer is not particularly limited and can be selected from the configurations exemplified for the positive electrode.

[0052] The negative electrode substrate has electrical conductivity. Metals such as copper, nickel, stainless steel, nickel-plated steel, and aluminum, or alloys thereof, carbon materials, etc. are used as the material of the negative electrode substrate. Among these, copper or copper alloys are preferred. Examples of the negative electrode substrate include foils, vapor deposition films, meshes, and porous materials, and foils are preferred from the viewpoint of cost. Therefore, copper foil or copper alloy foil is preferred as the negative electrode substrate. Examples of copper foil include rolled copper foil and electrolytic copper foil.

[0053] The average thickness of the negative electrode substrate is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, further preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By setting the average thickness of the negative electrode substrate within the above range, it is possible to increase the strength of the negative electrode substrate and to increase the energy density per volume of the nonaqueous electrolyte storage element.

[0054] <Negative electrode active material layer> The negative electrode active material layer contains a negative electrode active material. The negative electrode active material layer contains optional components such as a conductive agent, a binder, a thickener, a filler, etc., as necessary. The optional components such as a conductive agent, a binder, a thickener, a filler, etc. can be selected from the materials exemplified for the positive electrode above.

[0055] The negative electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W as components other than the negative electrode active material, conductive agent, binder, thickener, and filler.

[0056] The negative electrode active material can be appropriately selected from known negative electrode active materials. A material capable of absorbing and releasing lithium ions is usually used as the negative electrode active material for lithium ion secondary batteries. Examples of the negative electrode active material include metal Li; metals or semimetals such as Si and Sn; metal oxides or semimetal oxides such as Si oxide, Ti oxide, and Sn oxide; Li4Ti5O 12 , LiTiO 2、Examples of the material include titanium-containing oxides such as TiNb2O7, polyphosphate compounds, silicon carbide, and carbon materials such as graphite and non-graphitic carbon (easily graphitized carbon or non-graphitizable carbon). Among these materials, graphite or non-graphitic carbon is preferred, and graphite is more preferred, from the viewpoint of favorably forming a coating derived from an unsaturated cyclic carbonate that protects the surface of the negative electrode active material. In the negative electrode active material layer, one of these materials may be used alone, or two or more of them may be used in combination.

[0057] "Graphite" refers to graphite that has an average lattice spacing (d 002 ) is 0.33 nm or more and less than 0.34 nm. Examples of graphite include natural graphite and artificial graphite. Artificial graphite is preferred from the viewpoint of availability of materials with stable physical properties.

[0058] "Non-graphitic carbon" refers to carbon that has an average lattice spacing (d 002 ) is 0.34 nm or more and 0.42 nm or less. Examples of non-graphitizable carbon include non-graphitizable carbon and graphitizable carbon. Examples of non-graphitizable carbon include resin-derived materials, petroleum pitch or petroleum pitch-derived materials, petroleum coke or petroleum coke-derived materials, plant-derived materials, and alcohol-derived materials.

[0059] Here, the "discharged state" of the carbon material means a state in which the carbon material, which is the negative electrode active material, is discharged so that lithium ions that can be absorbed and released during charging and discharging are sufficiently released from the carbon material, which is the negative electrode active material. For example, in a half cell using a negative electrode containing a carbon material as a negative electrode active material as a working electrode and metallic Li as a counter electrode, the open circuit voltage is 0.7 V or more.

[0060] "Non-graphitizable carbon" means the above d 002 This refers to carbon materials with a particle size of 0.36 nm or more and 0.42 nm or less.

[0061] "Graphitizable carbon" means the above d 002This refers to carbon materials with a particle size of 0.34 nm or more and less than 0.36 nm.

[0062] The negative electrode active material is usually a particle (powder). The average particle size of the negative electrode active material can be, for example, 1 nm or more and 100 μm or less. When the negative electrode active material is a carbon material, a titanium-containing oxide, or a polyphosphate compound, the average particle size may be 1 μm or more and 100 μm or less. When the negative electrode active material is Si, Sn, Si oxide, Sn oxide, or the like, the average particle size may be 1 nm or more and 1 μm or less. By setting the average particle size of the negative electrode active material to the above lower limit or more, the production or handling of the negative electrode active material becomes easy. By setting the average particle size of the negative electrode active material to the above upper limit or less, the electronic conductivity of the negative electrode active material layer is improved. The method of obtaining powder with a predetermined particle size can be selected from the methods exemplified for the positive electrode. When the negative electrode active material is a metal such as metallic Li, the negative electrode active material layer may be in the form of a foil.

[0063] The content of the negative electrode active material in the negative electrode active material layer is preferably 60% by mass to 99% by mass, more preferably 90% by mass to 98% by mass. By setting the content of the negative electrode active material in the above range, both high energy density and manufacturability of the negative electrode active material layer can be achieved.

[0064] The content of the conductive agent in the negative electrode active material layer can be, for example, 0.1% by mass or more and 5% by mass or less. The content of the conductive agent in the negative electrode active material layer may be 3% by mass or less or 1% by mass or less, and the negative electrode active material layer may not contain a conductive agent.

[0065] The content of the binder in the negative electrode active material layer is preferably 0.5% by mass to 5% by mass, more preferably 0.8% by mass to 5% by mass. By setting the content of the binder in the above range, the graphite particles and the like can be stably held.

[0066] The content of the thickener in the negative electrode active material layer is, for example, preferably from 0.1% by mass to 6% by mass, and more preferably from 0.5% by mass to 3% by mass.

[0067] The content of the filler in the negative electrode active material layer may be, for example, 0.1% by mass to 8% by mass, or 0.5% by mass to 5% by mass. The content of the filler in the negative electrode active material layer may be 3% by mass or less, or 1% by mass or less, and the negative electrode active material layer may not contain a filler.

[0068] The lower limit of the BET specific surface area of ​​the negative electrode active material layer is 1.0 m 2 / g is preferred, and 2.0m 2 / g is more preferable, and 3.0m 2 / g (e.g. 4.0m 2 On the other hand, the upper limit of the BET specific surface area of ​​the negative electrode active material layer is 10.0 m 2 / g is preferred, 6.0m 2 / g is more preferable, and 5.0m 2 / g (e.g. 4.5m 2 / g) is more preferable. By using a negative electrode active material layer having the above BET specific surface area, the above-mentioned effects can be more preferably exhibited. The BET specific surface area of ​​the negative electrode active material layer may be equal to or greater than any of the above-mentioned lower limits and equal to or less than any of the above-mentioned upper limits. The BET specific surface area of ​​the negative electrode active material layer can be adjusted by the particle size of the negative electrode active material, the heat treatment conditions of the negative electrode active material, whether or not pressing is performed during the production of the negative electrode, the pressure of the pressing, and the like.

[0069] [Separator] The separator can be appropriately selected from known separators. For example, a separator consisting of only a substrate layer, a separator in which a heat-resistant layer containing heat-resistant particles and a binder is formed on one or both surfaces of the substrate layer, etc. can be used as the separator. Examples of the shape of the substrate layer of the separator include woven fabric, nonwoven fabric, and porous resin film. Among these shapes, a porous resin film is preferred from the viewpoint of strength, and a nonwoven fabric is preferred from the viewpoint of non-aqueous electrolyte retention. As the material of the substrate layer of the separator, polyolefins such as polyethylene and polypropylene are preferred from the viewpoint of shutdown function, and polyimide and aramid are preferred from the viewpoint of oxidation decomposition resistance. A material obtained by combining these resins may be used as the substrate layer of the separator.

[0070] The heat-resistant particles contained in the heat-resistant layer preferably have a mass loss of 5% or less when heated from room temperature to 500°C under an air atmosphere at 1 atmosphere, and more preferably have a mass loss of 5% or less when heated from room temperature to 800°C. Examples of materials with a mass loss of a predetermined amount or less include inorganic compounds. Examples of inorganic compounds include oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate; nitrides such as aluminum nitride and silicon nitride; carbonates such as calcium carbonate; sulfates such as barium sulfate; sparingly soluble ion crystals such as calcium fluoride, barium fluoride, and barium titanate; covalent crystals such as silicon and diamond; mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or artificial products thereof. As the inorganic compound, these substances may be used alone or in the form of a complex, or two or more of them may be mixed and used. Among these inorganic compounds, silicon oxide, aluminum oxide, or aluminosilicate is preferred from the viewpoint of the safety of the nonaqueous electrolyte storage element.

[0071] The porosity of the separator is preferably 80% by volume or less from the viewpoint of strength, and is preferably 20% by volume or more from the viewpoint of discharge performance. Here, "porosity" refers to a volume-based value measured with a mercury porosimeter.

[0072] As the separator, a polymer gel composed of a polymer and an electrolyte may be used. Examples of the polymer include polyacrylonitrile, polyethylene oxide, polypropylene oxide, polymethyl methacrylate, polyvinyl acetate, polyvinylpyrrolidone, and polyvinylidene fluoride. The use of the polymer gel has an effect of suppressing leakage. As the separator, the above-mentioned porous resin film or nonwoven fabric may be used in combination with the polymer gel.

[0073] [Non-aqueous electrolyte] The non-aqueous electrolyte contains an unsaturated cyclic carbonate and a dinitrile compound.

[0074] The unsaturated cyclic carbonate is a cyclic carbonate having a carbon-carbon unsaturated bond in the molecule. The unsaturated cyclic carbonate may be a cyclic carbonate having a carbon-carbon double bond in the molecule. As the unsaturated cyclic carbonate, an unsaturated cyclic carbonate having 3 to 15 carbon atoms (for example, 3 to 12, preferably 3 to 9, more preferably 3 to 6) may be preferably used. The number of carbon-carbon double bonds in the unsaturated cyclic carbonate is not particularly limited as long as it is one or more, but may be, for example, 1 to 3, preferably 1 or 2 (for example, 1). The unsaturated cyclic carbonate may be one in which some or all of the hydrogen atoms are substituted with other groups or elements (for example, fluorine atoms). The unsaturated cyclic carbonate may be one in which some or all of the hydrogen atoms are substituted with other groups or elements. Examples of unsaturated cyclic carbonates having a carbon-carbon double bond in a ring structure include vinylene carbonate, 1-phenylvinylene carbonate, 1,2-diphenylvinylene carbonate, fluorovinylene carbonate, methylvinylene carbonate, fluoromethylvinylene carbonate, ethylvinylene carbonate, propylvinylene carbonate, butylvinylene carbonate, dimethylvinylene carbonate, diethylvinylene carbonate, dipropylvinylene carbonate, and trifluoromethylvinylene carbonate. Examples of cyclic carbonates having a carbon-carbon double bond in a portion other than the ring structure include vinylethylene carbonate and styrene carbonate. As the unsaturated cyclic carbonate, those having a carbon-carbon unsaturated bond in a ring structure are preferred, and vinylene carbonate is more preferred. One or more types of unsaturated cyclic carbonates can be used.

[0075] The content of the unsaturated cyclic carbonate in the non-aqueous electrolyte is preferably 0.1% by mass or more and 10% by mass or less. When the content of the unsaturated cyclic carbonate in the non-aqueous electrolyte is in the above range, a good coating containing an appropriate amount of a component derived from the unsaturated cyclic carbonate is formed on the surface of the negative electrode active material, thereby making it possible to increase the capacity retention rate after long-term storage. The lower limit of the content of the unsaturated cyclic carbonate in the non-aqueous electrolyte is 0.02 mol / dm at 20° C. and 1 atmosphere. 3 , 0.04mol / dm 3 , 0.10 mol / dm 3 , 0.15 mol / dm 3 or 0.22 mol / dm 3 The upper limit of the content of the unsaturated cyclic carbonate in the nonaqueous electrolyte is 1.0 mol / dm at 20° C. and 1 atmosphere from the viewpoint of increasing the initial output. 3 , 0.5 mol / dm 3 or 0.3 mol / dm 3 The content of the unsaturated cyclic carbonate in the nonaqueous electrolyte may be equal to or greater than any one of the above-mentioned lower limits and equal to or less than any one of the above-mentioned upper limits.

[0076] Surface area of ​​the negative electrode active material layer S [m 2 ] to the amount A of unsaturated cyclic carbonate in the nonaqueous electrolyte C [mmol] Ratio A C The upper limit of / S is 0.164 mmol / m 2 Less than 0.150 mmol / m 2 is preferred, and 0.120 mmol / m 2 More preferably, 0.100 mmol / m 2 (For example, 0.085 mmol / m 2 On the other hand, the above ratio A C The lower limit of / S is 0.010 mmol / m 2 is preferred, and 0.020 mmol / m 2 More preferably, 0.030 mmol / m 2 More preferably, 0.055 mmol / m 2 More than (e.g. 0.060mmol / m 2) is even more preferable. C By setting the ratio A / S to the above upper limit or less, the coating film containing the component derived from the unsaturated cyclic carbonate on the surface of the negative electrode active material becomes appropriately thin, so that the initial output of the nonaqueous electrolyte storage element is improved and the effect of the present configuration of increasing the capacity retention rate after long-term storage is effectively exhibited. C By setting the ratio A / S to the above lower limit or more, the capacity retention rate after long-term storage can be further increased. C / S may be equal to or greater than any of the lower limits and equal to or less than any of the upper limits. C / S is, for example, 0.010 mmol / m 2 More than 0.164mmol / m 2 Less than (e.g. 0.055 mmol / m 2 More than 0.120mmol / m 2 Below, 0.055mmol / m 2 More than 0.100mmol / m 2 Less than or equal to 0.060mmol / m 2 More than 0.085mmol / m 2 The above ratio A is preferably used. C A nonaqueous electrolyte storage element having / S can achieve both high initial output and excellent capacity retention rate after long-term storage at a high level.

[0077] The dinitrile compound is not particularly limited as long as it has two cyano groups in the molecule. The dinitrile compound may have a chain structure having cyano groups at both ends of the molecule. The dinitrile compound may also be a compound represented by the chemical formula [CN-R-CN]. In the above chemical formula, R is a saturated or unsaturated hydrocarbon group having 1 to 10 carbon atoms. The hydrocarbon group may contain a halogen atom (e.g., a fluorine atom). R is preferably an alkylene group. In addition, from the viewpoint of efficiently chelating the transition metal element cation derived from the lithium transition metal compound between the two cyano groups, the number of carbon atoms of R is preferably 2 to 6, more preferably 2 to 4, and even more preferably 2.

[0078] Examples of dinitrile compounds include succinonitrile, adiponitrile, glutaronitrile, malononitrile, pimelonitrile, suberonitrile, azelanitrile, sebaconitrile, undecanedinitrile, and dodecanedinitrile. Among these, succinonitrile or adiponitrile is preferred, and succinonitrile is more preferred. One or more dinitrile compounds can be used.

[0079] The content of the dinitrile compound in the non-aqueous electrolyte is preferably 0.1% by mass or more and 10% by mass or less. When the content of the dinitrile compound in the non-aqueous electrolyte is within the above range, the transition metal element cation derived from the lithium transition metal compound can be sufficiently chelated. The lower limit of the content of the dinitrile compound in the non-aqueous electrolyte is 0.01 mol / dm at 20° C. and 1 atm. 3 , 0.03 mol / dm 3 or 0.05 mol / dm 3 (For example, 0.06 mol / dm 3 or 0.08 mol / dm 3 In some embodiments, the lower limit of the content of the dinitrile compound in the nonaqueous electrolyte is 0.10 mol / dm 3 , 0.12 mol / dm 3 or 0.15 mol / dm 3 By setting the content of the dinitrile compound in the non-aqueous electrolyte to be equal to or more than the above lower limit, the above-mentioned effects can be more effectively exhibited. The upper limit of the content of the dinitrile compound in the non-aqueous electrolyte is 1.0 mol / dm at 20° C. and 1 atmosphere from the viewpoint of increasing the input power retention rate after long-term storage. 3 , 0.5 mol / dm 3 or 0.3 mol / dm 3 (For example, 0.2 mol / dm 3 In some embodiments, the upper limit of the content of the dinitrile compound in the nonaqueous electrolyte is 0.15 mol / dm 3 , 0.12 mol / dm 3 or 0.10 mol / dm 3The content of the dinitrile compound in the nonaqueous electrolyte may be equal to or greater than any one of the above-mentioned lower limits and equal to or less than any one of the above-mentioned upper limits.

[0080] Amount A of the lithium transition metal compound in the positive electrode L [mmol] vs. the amount of dinitrile compound in the non-aqueous electrolyte A N [mmol] Ratio A N / A L The lower limit of the ratio A is 0.010, and preferably 0.012. N / A L The lower limit of the ratio A may be 0.016 or 0.020. N / A L By making the ratio A equal to or greater than the lower limit, the cations derived from the lithium transition metal compound can be sufficiently chelated, and the capacity retention rate after long-term storage can be increased. N / A L The upper limit of the ratio A is not particularly limited, but may be set to, for example, 0.100. N / A L The upper limit of the ratio A may be 0.080, 0.050, or 0.030. N / A L By setting the ratio A to be equal to or less than the upper limit, the handleability of the nonaqueous electrolyte and the manufacturability of the nonaqueous electrolyte storage element can be improved, and the input power retention rate after long-term storage can be increased. N / A L may be equal to or greater than any of the lower limits described above and equal to or less than any of the upper limits described above.

[0081] The non-aqueous electrolyte is usually a non-aqueous electrolytic solution. The non-aqueous electrolytic solution contains a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous electrolytic solution contains an unsaturated cyclic carbonate and a dinitrile compound as additives (components other than the electrolyte salt and the non-aqueous solvent).

[0082] The non-aqueous solvent can be appropriately selected from known non-aqueous solvents. Examples of the non-aqueous solvent include cyclic carbonates, chain carbonates, carboxylates, phosphates, sulfonates, ethers, amides, etc. As the non-aqueous solvent, those in which some of the hydrogen atoms contained in these compounds are replaced with halogens may be used. Note that the unsaturated cyclic carbonates that are additives are not considered to be non-aqueous solvents.

[0083] Examples of the cyclic carbonate include saturated cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), chloroethylene carbonate, fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), etc. Among these, EC is preferred.

[0084] Examples of the chain carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diphenyl carbonate, trifluoroethyl methyl carbonate, bis(trifluoroethyl) carbonate, etc. Among these, EMC is preferable.

[0085] As the non-aqueous solvent, it is preferable to use a cyclic carbonate or a chain carbonate, and it is more preferable to use a combination of a cyclic carbonate and a chain carbonate. By using a cyclic carbonate, it is possible to promote dissociation of the electrolyte salt and improve the ionic conductivity of the non-aqueous electrolyte. By using a chain carbonate, it is possible to keep the viscosity of the non-aqueous electrolyte low. When using a cyclic carbonate and a chain carbonate in combination, it is preferable that the volume ratio of the cyclic carbonate to the chain carbonate (cyclic carbonate:chain carbonate) is, for example, in the range of 5:95 to 50:50.

[0086] The electrolyte salt can be appropriately selected from known electrolyte salts. Examples of the electrolyte salt include lithium salts, sodium salts, potassium salts, magnesium salts, onium salts, etc. Among these, lithium salts are preferred.

[0087] Examples of the lithium salt include inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, and LiN(SO2F)2, lithium oxalate salts such as lithium bis(oxalate)borate (LiBOB), lithium difluorooxalateborate (LiFOB), and lithium bis(oxalate)difluorophosphate (LiFOP), and lithium salts having a halogenated hydrocarbon group such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, and LiC(SO2C2F5)3. Among these, inorganic lithium salts are preferred, and LiPF6 is more preferred.

[0088] The electrolyte salt content in the non-aqueous electrolyte is 0.1 mol / dm at 20°C and 1 atmosphere. 3 More than 2.5mol / dm 3 It is preferable that the value is 0.3 mol / dm or less. 3 More than 2.0mol / dm 3 More preferably, it is 0.5 mol / dm or less. 3 More than 1.7mol / dm 3 More preferably, it is 0.7 mol / dm or less. 3 More than 1.5mol / dm 3 By setting the content of the electrolyte salt within the above range, the ionic conductivity of the non-aqueous electrolyte can be increased.

[0089] The non-aqueous electrolyte may contain components other than the unsaturated cyclic carbonate, the dinitrile compound, the non-aqueous solvent, and the electrolyte salt. Examples of other components include halogenated carbonates such as fluoroethylene carbonate (FEC) and difluoroethylene carbonate (DFEC); oxalates such as lithium bis(oxalate)borate (LiBOB), lithium difluorooxalateborate (LiFOB), and lithium bis(oxalate)difluorophosphate (LiFOP); imide salts such as lithium bis(fluorosulfonyl)imide (LiFSI); aromatic compounds such as biphenyl, alkylbiphenyl, terphenyl, partially hydrogenated terphenyl, cyclohexylbenzene, t-butylbenzene, t-amylbenzene, diphenyl ether, and dibenzofuran; partial halides of the aromatic compounds such as 2-fluorobiphenyl, o-cyclohexylfluorobenzene, and p-cyclohexylfluorobenzene; halogenated anisole compounds such as 2,4-difluoroanisole, 2,5-difluoroanisole, 2,6-difluoroanisole, and 3,5-difluoroanisole; succinic anhydride, glutaric anhydride, and the like. Acid, maleic anhydride, citraconic anhydride, glutaconic anhydride, itaconic anhydride, cyclohexanedicarboxylic anhydride; ethylene sulfite, propylene sulfite, dimethyl sulfite, methyl methanesulfonate, busulfan, methyl toluenesulfonate, dimethyl sulfate, ethylene sulfate, sulfolane, dimethyl sulfone, diethyl sulfone, dimethyl sulfoxide, diethyl sulfoxide, tetramethylene sulfoxide, diphenyl sulfide, 4,4'-bis(2,2-dioxo-1,3,2-dioxathi oran), 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiolane, thioanisole, diphenyl disulfide, dipyridinium disulfide, 1,3-propene sultone, 1,3-propane sultone, 1,4-butane sultone, 1,4-butene sultone, perfluorooctane, tristrimethylsilyl borate, tristrimethylsilyl phosphate, tetrakistrimethylsilyl titanate, lithium monofluorophosphate, lithium difluorophosphate, etc. These additives may be used alone or in combination of two or more.

[0090] The content of other components contained in the nonaqueous electrolyte is preferably 0.01% by mass to 10% by mass, more preferably 0.1% by mass to 7% by mass, even more preferably 0.2% by mass to 5% by mass, and particularly preferably 0.3% by mass to 3% by mass. By setting the content of other components within the above ranges, it is possible to improve the capacity retention performance or cycle performance after high-temperature storage, and to further improve safety.

[0091] The non-aqueous electrolyte may be a solid electrolyte, or a non-aqueous electrolyte solution and a solid electrolyte may be used in combination.

[0092] The solid electrolyte can be selected from any material that has ionic conductivity such as lithium, sodium, calcium, etc., and is solid at room temperature (e.g., 15° C. to 25° C.). Examples of the solid electrolyte include sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes, and polymer solid electrolytes.

[0093] As the sulfide solid electrolyte, in the case of a lithium ion secondary battery, for example, Li2S-P2S5, LiI-Li2S-P2S5, Li 10 Ge-P2S 12 etc.

[0094] The shape of the nonaqueous electrolyte storage element of this embodiment is not particularly limited, and examples thereof include a cylindrical battery, a prismatic battery, a flat battery, a coin battery, and a button battery.

[0095] Fig. 1 shows a nonaqueous electrolyte storage element 1 as an example of a prismatic battery. The figure is a see-through view of the inside of the container. An electrode body 2 having a positive electrode and a negative electrode wound with a separator sandwiched therebetween is housed in a prismatic container 3. The positive electrode is electrically connected to a positive electrode terminal 4 via a positive electrode lead 41. The negative electrode is electrically connected to a negative electrode terminal 5 via a negative electrode lead 51.

[0096] [Electricity storage device] The nonaqueous electrolyte storage element of the present embodiment can be mounted as an electricity storage unit (battery module) comprising a plurality of nonaqueous electrolyte storage elements assembled together in automobile power sources such as electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), etc., power sources for electronic devices such as personal computers and communication terminals, or power storage power sources, etc. In this case, the technology of the present invention may be applied to at least one nonaqueous electrolyte storage element included in the electricity storage unit.

[0097] 2 shows an example of an electricity storage device 30 in which electricity storage units 20, each of which is an assembly of two or more electrically connected nonaqueous electrolyte electricity storage elements 1, are further assembled. The electricity storage device 30 may include a bus bar (not shown) that electrically connects two or more nonaqueous electrolyte electricity storage elements 1, a bus bar (not shown) that electrically connects two or more electricity storage units 20, and the like. The electricity storage unit 20 or the electricity storage device 30 may include a status monitoring device (not shown) that monitors the status of one or more nonaqueous electrolyte electricity storage elements.

[0098] [Method of manufacturing the energy storage element] The method for producing the nonaqueous electrolyte storage element of the present embodiment can be appropriately selected from known methods. The method for producing the nonaqueous electrolyte storage element of the present embodiment includes, for example, preparing an electrode body, preparing a nonaqueous electrolyte, and housing the electrode body and the nonaqueous electrolyte in a container. The preparation of the electrode body includes preparing a positive electrode and a negative electrode, and forming the electrode body by stacking or rolling the positive electrode and the negative electrode with a separator interposed therebetween.

[0099] The method of housing the non-aqueous electrolyte in the container can be appropriately selected from known methods. For example, when a non-aqueous electrolyte solution is used as the non-aqueous electrolyte, the non-aqueous electrolyte solution may be injected through an injection port formed in the container, and then the injection port may be sealed.

[0100] [Other embodiments] The nonaqueous electrolyte storage element of the present invention is not limited to the above-described embodiment, and various modifications may be made without departing from the scope of the present invention. For example, the configuration of one embodiment may be added to the configuration of another embodiment, and part of the configuration of one embodiment may be replaced with the configuration of another embodiment or a well-known technique. Furthermore, part of the configuration of one embodiment may be deleted. Also, a well-known technique may be added to the configuration of one embodiment.

[0101] In the above embodiment, the nonaqueous electrolyte storage element is used as a chargeable and dischargeable nonaqueous electrolyte secondary battery (e.g., a lithium ion secondary battery), but the type, shape, size, capacity, etc. of the nonaqueous electrolyte storage element are arbitrary. The present invention can also be applied to various secondary batteries, electric double layer capacitors, lithium ion capacitors, and other capacitors. EXAMPLES

[0102] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0103] [Reference example 1] (Preparation of positive electrode) First, carbon-coated positive electrode active material particles were prepared by the following procedure. Lithium hydroxide monohydrate, diammonium hydrogen phosphate, and iron sulfate heptahydrate were weighed out so that the molar ratio of Li:Fe:P was 3:1:1, and mixed in ion-exchanged water to prepare a solution. Next, this solution was transferred to a polytetrafluoroethylene container, which was then placed in a pressure-resistant hydrothermal reaction vessel. After the inside of the hydrothermal reaction vessel was thoroughly replaced with nitrogen gas and sealed, hydrothermal synthesis was performed by heating at 170°C for 15 hours. After the hydrothermal synthesis, the product was naturally cooled to room temperature, and the resulting product was thoroughly washed with ion-exchanged water and then dried under reduced pressure at 120°C for 6 hours to obtain particles of lithium iron phosphate, a lithium transition metal compound having a polyanion structure. Thereafter, in order to form a carbon coating layer that coats the lithium iron phosphate particles, the lithium iron phosphate particles and polyvinyl alcohol, which is a carbon source, were mixed in ion-exchanged water, and the mixture was subjected to a bead mill treatment for 2 hours using zirconia beads having a diameter of 0.1 mm, and wet-pulverized. The mixing ratio of the lithium iron phosphate particles and polyvinyl alcohol was adjusted so that the ratio of the carbon coating layer to the carbon-coated positive electrode active material particles was 1.2 mass%. The mixture of the lithium iron phosphate particles and polyvinyl alcohol was spray-dried using a spray dryer to obtain a granulated dry powder. As a final step, the dry powder was heated in a tubular furnace under nitrogen gas flow at 720°C for 2 hours to obtain carbon-coated positive electrode active material particles. A positive electrode mixture paste was prepared using the carbon-coated positive electrode active material particles, acetylene black (AB) as a conductive agent, polyvinylidene fluoride (PVDF) as a binder, and N-methylpyrrolidone (NMP) as a dispersion medium. The mass ratio of the carbon-coated positive electrode active material particles, AB, and PVDF was 90:5:5 in terms of solid content. This positive electrode mixture paste was applied to both sides of an aluminum foil as a positive electrode substrate, and dried. A roll press was performed to obtain a positive electrode in which a positive electrode active material layer was laminated on both sides of the positive electrode substrate.

[0104] (Preparation of negative electrode) A negative electrode mixture paste was prepared by mixing graphite as a negative electrode active material, styrene-butadiene rubber (SBR) as a binder, carboxymethyl cellulose (CMC) as a thickener, and water as a dispersion medium. The mass ratio of graphite, SBR, and CMC was 96:3.3:0.7 in terms of solid content. This negative electrode mixture paste was applied to both sides of copper foil as a negative electrode substrate, and dried. Then, roll pressing was performed to obtain a negative electrode in which a negative electrode active material layer was laminated on both sides of the negative electrode substrate. The BET specific surface area of ​​the negative electrode active material layer was 3.33 m 2 / g.

[0105] (Non-aqueous electrolyte) A mixture of ethylene carbonate (EC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC) in a volume ratio of 30:35:35 was added to the solvent at a concentration of 1.1 mol / dm 3A solution was obtained by dissolving LiPF6 at a concentration of 1.0% by mass. Vinylene carbonate (VC) was further dissolved as an additive in the obtained solution at a content of 1.0% by mass to prepare a non-aqueous electrolyte.

[0106] (Fabrication of non-aqueous electrolyte storage element) The total mass of the negative electrode active material layer is calculated by the surface area S [m 2 ] to the amount of VC in the non-aqueous electrolyte A C [mmol] Ratio A C / S is 0.55mmol / m 2 After adjusting the thickness of the positive electrode and the negative electrode to be the same, the positive electrode and the negative electrode were stacked together with a polyolefin microporous film as a separator therebetween to prepare an electrode assembly. The electrode assembly was placed in a container made of a metal resin composite film, and the nonaqueous electrolyte was poured into the container, which was then sealed by heat welding to obtain a nonaqueous electrolyte storage element of Reference Example 1.

[0107] [Reference Examples 2 to 4] Each of the nonaqueous electrolyte storage elements of Reference Examples 2 to 4 was obtained in the same manner as Reference Example 1, except that the VC content in the nonaqueous electrolyte was as shown in Table 1. In the following description, including Table 1 and Tables 2 and 3 described later, vinylene carbonate and succinonitrile, which are additives in the nonaqueous electrolyte, are abbreviated as "VC" and "NR," respectively, and A N / A L is the amount of lithium transition metal compound A L Amount of succinonitrile in non-aqueous electrolyte A versus [mmol] N The ratio is in [mmol].

[0108] [Examples 1 and 2 and Comparative Example 1] The BET specific surface area of ​​the negative electrode active material layer was changed as shown in Table 2, and the contents of VC and NR in the non-aqueous electrolyte, A C / S and A N / A LThe nonaqueous electrolyte storage elements of Examples 1 and 2 and Comparative Example 1 were obtained in the same manner as in Reference Example 1, except that the was as shown in Table 2. The BET specific surface area of ​​the negative electrode active material layer was changed by adjusting the heat treatment conditions when producing the negative electrode active material. That is, negative electrode active materials having different BET specific surface areas were produced by adjusting the heat treatment conditions, and negative electrode active material layers having different BET specific surface areas were prepared using these.

[0109] [Reference examples 5 and 6] The BET specific surface area of ​​the negative electrode active material layer was changed as shown in Table 3, and the contents of VC and NR in the non-aqueous electrolyte, A C / S and A N / A L The nonaqueous electrolyte storage elements of Reference Examples 5 and 6 were obtained in the same manner as Reference Example 1, except that the masses of the positive electrode, negative electrode, and nonaqueous electrolyte were changed as shown in Table 3. The BET specific surface area of ​​the negative electrode active material layer was changed by adjusting the heat treatment conditions when producing the negative electrode active material. That is, negative electrode active materials having different BET specific surface areas were produced by adjusting the heat treatment conditions, and negative electrode active material layers having different BET specific surface areas were prepared using these materials. In Reference Examples 5 and 6, the masses of the positive electrode, negative electrode, and nonaqueous electrolyte were changed from those of Reference Example 1.

[0110] [evaluation] (1)Initial charge / discharge The obtained nonaqueous electrolyte storage elements were initially charged and discharged at 25° C. in the following manner. Constant-current constant-voltage charging was performed with a charging current of 0.2 C and a charge cut-off voltage of 3.5 V. The charge was terminated until the charging current reached 0.01 C. A rest period of 10 minutes was then provided. Thereafter, constant-current discharging was performed with a discharging current of 0.2 C and a discharge cut-off voltage of 2.0 V.

[0111] (2) Initial capacity confirmation test Next, an initial capacity confirmation test was performed on each nonaqueous electrolyte storage element at 25° C. in the following manner. Constant current and constant voltage charging was performed with a charging current of 1.0 C and a charge cut-off voltage of 3.5 V. The charge was terminated until the charging current reached 0.01 C. A rest period of 10 minutes was then provided. Then, constant current discharging was performed with a discharging current of 1.0 C and a discharge cut-off voltage of 2.0 V. The discharge capacity at this time was defined as the "initial discharge capacity." The fully charged state based on the initial discharge capacity was defined as SOC (State Of Charge) 100%.

[0112] (3) Initial output confirmation test After the initial capacity confirmation test, each nonaqueous electrolyte storage element was charged at a constant current of 0.2C in a thermostatic chamber at 25°C until the SOC reached 50%. Next, the element was discharged for 60 seconds at discharge currents of 0.2C, 0.5C, and 1.0C. After a 10-minute rest period, the element was supplementarily charged at a charge current of 0.2C until the SOC reached 50%. From the current-voltage characteristic graph obtained by plotting the voltage 10 seconds after the start of each discharge on the vertical axis and the discharge current on the horizontal axis, the output [W] at 10 seconds was determined by the IV method with a lower limit voltage of 2.0V, and this was taken as the "initial output". Table 1 shows the percentage of initial output based on Reference Example 2, Table 2 shows the percentage of initial output based on Comparative Example 1, and Table 3 shows the percentage of initial output based on Reference Example 5.

[0113] (4) Preservation test After the above-mentioned initial output confirmation test, each nonaqueous electrolyte storage element was subjected to a storage test at 45° C. in the following manner. In a thermostatic chamber at 25°C, the battery was charged at a constant current of 1.0C until the SOC reached 90%. It was then stored in a thermostatic chamber at 45°C. Every 30 days, the battery was measured for performance in the same manner as in the initial capacity confirmation test and the initial output confirmation test, and supplementary charging was performed at a charging current of 1.0C until the SOC reached 90%. This was continued for 300 days.

[0114] (5) Capacity confirmation test after storage test For each nonaqueous electrolyte storage element after the storage test, a capacity confirmation test after the storage test was performed in the same manner as the initial capacity confirmation test. The discharge capacity at this time was designated as the "discharge capacity after the storage test." The percentage of the discharge capacity after the storage test to the initial discharge capacity for each nonaqueous electrolyte storage element is shown in Tables 1, 2, and 3 as the "capacity retention rate."

[0115] [Table 1]

[0116] [Table 2]

[0117] [Table 3]

[0118] As shown in Table 1, when the non-aqueous electrolyte does not contain NR, the amount A of VC in the non-aqueous electrolyte relative to the surface area S of the negative electrode active material layer is C Ratio of A C When A / S was reduced, the capacity retention rate after the storage test decreased, but the initial output of the nonaqueous electrolyte storage element increased. C / S is 0.164mmol / m 2 If the nonaqueous electrolyte contains NR, A N / A L In Examples 1 and 2 in which A was 0.010 or more, the capacity retention rate after the storage test was larger than that in Comparative Example 1 in which the nonaqueous electrolyte did not contain NR. C / S is 0.164mmol / m 2 In the above cases, Reference Example 5 in which the nonaqueous electrolyte does not contain NR and Reference Example 6 in which the nonaqueous electrolyte contains NR and N / A L The capacity retention rate after the storage test was the same in Reference Example 6 where A was 0.010 or more. CIt is considered that when / S is sufficiently small, the coating film formed by VC to protect the negative electrode surface is easily maintained in a good condition by the nonaqueous electrolyte containing a predetermined amount or more of NR. [Industrial Applicability]

[0119] The present invention can be applied to nonaqueous electrolyte electricity storage elements used as power sources for electronic devices such as personal computers and communication terminals, and automobiles. [Explanation of symbols]

[0120] 1. Non-aqueous electrolyte storage element 2 Electrode body 3 containers 4 Positive terminal 41 Positive lead 5 Negative terminal 51 Negative lead 20 Energy Storage Unit 30 Energy storage device

Claims

1. The battery comprises a positive electrode including a lithium transition metal compound having a polyanion structure, a negative electrode including a negative electrode active material layer including a negative electrode active material, and a non-aqueous electrolyte; The non-aqueous electrolyte contains an unsaturated cyclic carbonate and a dinitrile compound, The surface area S [m 2 ], the amount A of the unsaturated cyclic carbonate in the nonaqueous electrolyte C Ratio A [mmol] C / S is 0.164 mmol / m 2 is less than The amount A of the lithium transition metal compound in the positive electrode L The amount A of the dinitrile compound in the nonaqueous electrolyte relative to [mmol] N Ratio A [mmol] N / A L A nonaqueous electrolyte electricity storage element in which the value is 0.010 or more.

2. The above ratio A C / S is 0.055 mmol / m 2 The nonaqueous electrolyte storage element according to claim 1 , wherein the nonaqueous electrolyte is more than 100%.

3. 3. The nonaqueous electrolyte storage element according to claim 1, wherein the dinitrile compound is succinonitrile or adiponitrile.

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery and method for manufacturing the same

    JP2017097995A